Common Chicken Diseases in Smallholder Farming: A Review - Chanphanit Chut; Mardy Serey; Sokun Khoeun (International Journal of Integrative Research, 2023)
Smallholder chicken farming is an important source of food and income for millions of people around the world as well as in rural areas. However, chicken diseases can cause significant losses to smallholder farmers. The objective of this review is to discuss the most common chicken diseases in smallholder farming, and to discuss the challenges that smallholder farmers face in preventing and controlling chicken diseases. As methodology, this paper summarizes and synthesizes the existing research on the common chicken diseases in smallholder farming. The results showed that there are a variety of chicken diseases, which can be caused by viruses, bacteria, parasites, and fungi. One of the biggest challenges in preventing and controlling chicken diseases is the lack of access to veterinary care and vaccines for smallholder farmers. Another challenge is the lack of knowledge about chicken diseases among many smallholder farmers. However, chicken diseases can be prevented and controlled through a variety of measures, including: vaccination, biosecurity, and good management practices. For recommendation, farmers should avoid selecting seeds in the nest for breeding, and farmers should use animal feed that is self-produced and composed of existing raw materials in the village or district, especially farmers who should be adequately vaccinated against chicken disease